ASSESSMENT ON GROUPER FISHERIES WITH ECOSYSTEM APPROACH TO FISHERIES MANAGEMENT IN KARIMUNJAWA NATIONAL PARK - Beta Indi Sulistyowati; M Mukhlis Kamal; Yonvitner; Irfan Yulianto (Pusat Kajian Sumberdaya Pesisir dan Lautan IPB, 2018)
Groupers are member of family Serranidae that plays important role in ecology of coral reefs ecosystem as top level predators.Economically, groupers are targets species for their high economic values.Based on statistics data for Karimunjawa fisheries during 2010 to 2014 it is shown a decline in capture of groupers. This implies to the demand of better management. This study dealt with the appraisal of the groupers fisheries in Karimunjawa based on indicators assessment of the Ecosystem Approach Fisheries Management (EAFM). EAFM approach uses comprehensively both ecological, socio-economics as well as institutional and governance capacity in managing fisheries. The results showed that the groupers fisheries has been managed moderately (n=70.59), of which priority management plan started from social development strategy to maintain existing strategy. Keywords: Serranidae; Grouper Fisheries; EAFM; Management Plan